Arbuscular mycorrhizal fungal communities associated with coffee intercropped with grevillea - Roberta de Souza Santos; Divino Levi Miguel; Leandro Martins de Freitas; Fábia Giovana do Val de Assis; Valber Dias Teixeira; Karl Kemmelmeier; Sidney Luiz Stürmer; Patrícia Lopes Leal (Acta Botânica Brasílica)
ABSTRACT Arbuscular mycorrhizal fungi (AMF) communities in coffee-cultivated areas in the northeastern region of Brazil have been insufficiently studied when compared to other Brazilian regions. This study determined AMF occurrence and richness in coffee-cultivated soils under different management systems in the State of Bahia, Brazil, and in soils from surrounding areas with pasture and native forest (control areas). Physicochemical soil characteristics in the different study areas were also evaluated. A total of 43 AMF spore morphotypes in 14 genera belonging to six families were recovered from soil samples from all study areas: Glomeraceae (35%), Acaulosporaceae (35%), Gigasporaceae (21%), Ambisporaceae (5%), Archaeosporaceae (2%) and Diversisporaceae (2%). Rhizophagus fasciculatus, Acaulospora mellea and Glomus sp. 1 were the most frequent fungi found in all areas. In the coffee-cultivated areas, 12 genera were identified, two of which (Dominikia and Fuscutata) had not yet been reported in association with coffee plants in Brazil. We concluded that soil physicochemical properties and AMF occurrence can distinguish study areas based on land use. The different coffee management systems did not influence AMF species richness, but the occurrence was influenced by both management and soil factors.